Relgious Transformation in Digital Era: Mediatization Impact on Religious Practice - Natasha Constantin; Ardina Lukita Wiraputra; Geraldo Rotty; Desideria Lumongga Dwihadiah (Eduvest - Journal of Universal Studies, 2024)
In an increasingly advanced modern era and growing communication technology, mediatization is present in every aspect of people's lives, including in the context of religiosity. The transition to the use of new media in supporting religious activities to keep running faces challenges that are not easy with the issue of the sacredness of religious activities that are communal in nature at first and are forced to change formats. This research was conducted with a qualitative approach and supported by a literature review method and complemented by supporting data obtained from researcher observations of related phenomena that occur today. In the end, mediatization in the religious context is like a double-edged sword with all its advantages and challenges, especially for conventional religious leaders who are increasingly eroded in power and reach by influencers who are able to reach a stronger and wider audience.